Anesthetic Management of a Young Adult with Severe Rheumatic Mitral and Aortic Stenosis Undergoing Double Valve Replacement: A Case Report - Fauzul Nurul Azmi; Pelinggo Jaya; Vera Muharrami (HM Publisher, 2026)
Background. Rheumatic heart disease remains a leading cause of valvular pathology in young adults of low- and middle-income countries. The coexistence of severe mitral stenosis (MS) and severe aortic stenosis (AS) confronts the anesthesiologist with directly opposed hemodynamic imperatives and a markedly narrowed margin of safety, particularly during separation from cardiopulmonary bypass (CPB). Case presentation. A 41-year-old man presented with a 14-year history of exertional syncope, progressive dyspnea, orthopnea, and paroxysmal nocturnal dyspnea. Transthoracic echocardiography demonstrated severe rheumatic MS (mitral valve area 0.8 cm²) and severe rheumatic AS (aortic valve area 0.8 cm², mean gradient 56 mmHg) with preserved left ventricular ejection fraction (67%), reduced right ventricular contractility (TAPSE 17 mm), and atrial fibrillation. He underwent double valve replacement under general anesthesia using an opioid-based, hemodynamically stable induction with full invasive monitoring. Separation from CPB was complicated by two episodes of ventricular tachycardia requiring synchronized cardioversion (30 J and 20 J) and was managed with a milrinone–dobutamine–norepinephrine strategy. The patient was transferred ventilated to intensive care on inotropic and antiarrhythmic support and stabilized. Conclusion. Combined severe MS and AS demands an individualized plan reconciling contradictory goals: adequate preload and a controlled, unhurried heart rate for MS, against maintained afterload and coronary perfusion for AS. Meticulous invasive monitoring, a stable induction, anticipation of right ventricular dysfunction, and readiness for perioperative arrhythmia are decisive for a safe outcome.